2021
DOI: 10.1155/2021/8861038
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of a Cohort Study on the Association between Sleep Duration and Type 2 Diabetes Mellitus

Abstract: Objective. To study the association between sleep duration and the incidence of type 2 diabetes mellitus (T2DM) and to provide a theoretical basis for the prevention of T2DM through a meta-analysis. Methods. PubMed, Web of Science, Scopus, Embase, Cochrane Library, ProQuest, CNKI, Wanfang, VIP, and SINOMED were searched from their inception until May 2020. All cohort studies on the relationship between sleep duration and T2DM in adults were included. According to the inclusion and exclusion criteria, two autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…We found that most DAMs (flavonoids and phenolic acids) associated with the hypoglycemic function of C. paliurus leaves significantly accumulated in the 9 and 10 M groups and declined from the 10 M to the 11 M group, indicating that a suitable leaf-harvesting strategy for C. paliurus could be in September or October each year. T2DM is an expanding global health problem with a worldwide prevalence rate of 9.3% (463 million diabetic patients) in 2019, causing a huge crisis to health care systems around the world ( 42 ). Alpha-amylase is associated with the hydrolysis of starch into disaccharides, resulting in an increase in blood sugar levels ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that most DAMs (flavonoids and phenolic acids) associated with the hypoglycemic function of C. paliurus leaves significantly accumulated in the 9 and 10 M groups and declined from the 10 M to the 11 M group, indicating that a suitable leaf-harvesting strategy for C. paliurus could be in September or October each year. T2DM is an expanding global health problem with a worldwide prevalence rate of 9.3% (463 million diabetic patients) in 2019, causing a huge crisis to health care systems around the world ( 42 ). Alpha-amylase is associated with the hydrolysis of starch into disaccharides, resulting in an increase in blood sugar levels ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior publications suggested that the quantity of sleep was related to the future risk of type 2 diabetes mellitus (T2DM), but they were inconclusive. Although several meta-analyses have reported a U-shaped association between sleep duration and T2DM risk [7,8], other studies have indicated limited significance whether in short or long sleep [9][10][11][12]. This discrepancy could be related to the varied definitions of diabetes and the classification of sleep duration.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several meta-analyses on the risks of T2DM have also reported a U-shaped association with 7-8 hours of sleep associated with the lowest risk of T2DM. [9][10][11] According to a recent meta-analysis, habitual nappers were at a higher risk of all-cause mortality, while no significant association was found between daytime napping and cardiovascular disease. 12 Daytime napping for more than one hour was also associated with an increased risk of T2DM compared to nonnappers, in a meta-analysis of 4 cross-sectional and 6 cohort studies.…”
Section: Introductionmentioning
confidence: 99%